A business model for reinforcing the societal impact of publicly funded scholarly journals - Sivertsen, Gunnar (Septentrio Conference Series, 2014)
A large part of the scholarly journal articles from the humanities and social sciences at Norwegian research institutions are published in a small number of national or common Nordic journals. Many of these journals are sponsored by the Research Council of Norway on the national or Nordic level. The institutions that mainly contribute to the contents of the journals are also the main subscribers. The journals can be made open to society with only marginal extra costs for the institutions themselves and the sponsor.